Processing of Gelatin from the Skin of Pangasius hypopthalmus Using Papain Enzyme. Issue 1 (November 2021) - Suparmi, S; Edison, E; Meivayana, M
Abstract: This study aimed to determine the processing of gelatin of catfish skin using the papain enzyme in 3 different concentrations. The method used was an experiment with a factorial Completely Randomized Design (CRD). The experiment consisted of 2 factors, namely papain enzyme concentration and the immersion time of the enzyme with 3 replications. The first factor consisted of 3 levels, namely the use of papain enzymes P1 (2%), P2 (4%) and P3 (6%). The second factor, the immersion time consisted of 3 levels of 25 minutes (W1), 35 minutes (W2) and 45 minutes (W3). The data were analyzed by using CRD. The results showed that the combination of P2W1 showed the best viscosity and gel strength (6.77 CP and 115.17 g bloom).